Developing a Collaborative Recommendations Guide for Hybrid Software Development: A Focus Group Study - Andrade, Anielle S. Lisboa de; Quadros, Everton Luis Luz de; Fortes, Luciane Oliveira; Prikladnicki, Rafael (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2024: Anais do XXIII Simpósio Brasileiro de Qualidade de Software, 2024)
In the middle of the emergence of the COVID-19 pandemic, hybrid software development teams have notably gained prominence. However, coordinating these teams unveils many challenges, mainly around effective communication, the setup of a good working environment, and cooperative recommendations. To contribute to this field, we carried out a study to identify recommendations for managing hybrid software development teams within the IT department of a Brazilian multinational company. The study was in an industry-academia collaboration and was structured into three stages: (1) a multivocal literature review, (2) a case study containing discursive textual analysis through semi-structured interviews and non-participant observation (previously published), and (3) a focus group for the formulation of a collaborative recommendations guide - the stage we will present in this paper. We recruited 11 software engineers from eight software teams for the focus group. The study resulted in 23 recommendations categorized into three dimensions: individuals, processes, and spaces. We believe the recommendations can contribute to the growing knowledge of managing hybrid teams. The resultant guide also contributes to disseminating hybrid work strategies to the broader community, sharing insights for improving hybrid work in software teams and taking social and human aspects of work from anywhere in software development.